Aerodynamic Evaluation of a Symmetrical Airfoil Using Wind Tunnel Testing - Salem Fathi Elsheltat; Abdulbaset Ahmed Alshara; Walid Elshara (African Journal of Advanced Pure and Applied Sciences, 2024)
This research presents a detailed examination of the aerodynamic characteristics of a symmetrical airfoil through wind tunnel testing conducted at various angles of attack. The experiments carried out at the University of Hartford, were designed to evaluate how different angles of attack affect the airfoil’s aerodynamic properties, with particular focus on identifying the onset of stall conditions. The results demonstrated that the airfoil experiences a stall at a critical angle of attack of 21.8 degrees, marked by a sharp decline in lift and a simultaneous increase in drag, indicating substantial changes in aerodynamic forces. Observations made before and after this critical point provide essential insights into the shift from stable to unstable aerodynamic conditions, offering valuable information for optimizing airfoil designs in real-world applications. Beyond the experimental results, the study also includes a thorough review of various airfoil profiles and wind tunnel types, providing a comprehensive context for their relevance in aerodynamic research. The discussion covers the specific applications of different airfoil shapes and the benefits and drawbacks of different wind tunnel configurations, ranging from subsonic to transonic and supersonic flow conditions. By combining empirical data with an extensive literature review, this research provides a strong foundation for understanding the key factors influencing airfoil performance. The findings highlight the importance of accurately determining critical stall angles to enhance aircraft safety and efficiency, contributing significantly to the advancement of aerodynamic studies.